MiR-138-5p targeting LIMK1 suppresses breast cancer cell proliferation and motility. Issue 82 (9th November 2017) - Li, Dengfeng; Song, Hongming; Wu, Tianqi; Xie, Dan; Hu, Jiashu; Zhao, Junyong; Fang, Lin
Abstract : Breast cancer is the most frequently diagnosed female cancer. Abstract : Breast cancer is the most frequently diagnosed female cancer. LIM domain kinase 1 (LIMK1) was reported to increase breast cancer progressive biological behavior and was associated with clinical breast cancer outcomes. MiRNAs are a kind of small non-coding RNA that binds the target mRNAs, leading to protein downregulation. The aim of this study was to find whether miR-138-5p could target LIMK1 in breast cancer to suppress breast cancer biological behavior. The TCGA database showed that LIMK1 was highly expressed in breast cancer. The dual-luciferase report showed that LIMK1 was a target gene of miR-138-5p. Over-expression of miR-138-5p could significantly reduce expression of LIMK1 in mRNA and the protein level. Colony formation and MTT assay showed that over-expression of miR-138-5p could suppress proliferation of breast cancer cells. Wound-healing assay and transwell assay showed that over-expression of miR-138-5p could suppress migration and invasion of breast cancer cells. In addition, over-expression of miR-138-5p could arrest breast cancer cells into the G0/G1 phase by down-regulating expression of CDK4, 6/Cyclin D1 and CDK2/Cyclin E1 compounds. In conclusion, our study showed that miR-138-5p could target LIMK1 and suppress the progressive biological behavior of breast cancer cells. Mi-138-5p targeting LIMK1 may be a new potential treatment for breast cancer.